PEMAKAIAN BAHASA GAUL DALAM KOMUNIKASI DI JEJARING SOSIAL - Nanik Setyawati (Sasindo, 2014)
Social networking is a medium that is widely used by speakers of the language to communicate remotely via the internet. The use of the vocabulary of slang in social networks continues to grow and change to follow the trend. Social networks are much in demand by the public, ie facebook, twitter, BBM, and whats app. Slang vocabulary that developed lately are often irregular ie no formula or to abbreviate words. There is also the use of a foreign language. This language is temporal and confidential, then the impression that this language is the secret language of the thieves or criminals, but they are not. The confidentiality factor causing the vocabulary used in slang often changed. The use of slang in the form of communication in social networks such as: (a) the word irregular and can not be formulated, (b) tend to abbreviate words, and (c) using particles. Factors behind the use of slang in social networking is (a) to strengthen the relationship, look for a form of identity, expressing self-expression; (b) to convey things that are considered to be closed for any other age group or that the other party can not know what he was talking about; and (c) for the purpose of concealment or antics.Keywords: slang, social networking